Implementation of Waste Processing from the Source by the Traditional Village of Cagaan, Tampaksiring District, Gianyar Bali - Made Yaya Sawitri; Dewa Ketut Suryawan; Anak Agung Sagung Putri Risa Andriani (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2020)
The Caga Traditional Village, which is located in Pejeng Kangin Village, Tampak Siring District, is one of the traditional villages that is currently seriously developing the village's potential as a tourist village. One of the efforts to improve that is now being promoted is regarding the cleanliness of the village. However, currently there is no comprehensive system capable of managing most of the waste generated by villagers. This village already has a waste bank but it only manages around 30% of the total waste generated. Organic waste which is much larger in quantity is still dumped in the "teba" or backyard. Another problem is the presence of residual waste, which has so far been collected and then transported to a landfill (TPS). The problem raised in this "community service program" is the public's ignorance of government policies regarding waste management and the proper procedures for managing waste from sources. Therefore, to support the government's efforts in realizing a waste management system from sources and to support the efforts of traditional villages to develop their potential as a tourism village, education on waste management from sources in the traditional village of Caga, Pejeng Kangin was implemented. Activities that have been carried out include the socialization of government regulations regarding waste processing at the source, optimization of waste banks, and processing of organic waste using the composting method. The implementation of Waste Processing from the Source by the Traditional Village of Caga, Tampaksiring District, Gianyar " received a good reception from the community and full support from the management of the Caga Traditional Village.